Cataract Surgery with a Refractive Corneal Inlay in Place - N. R. Stojanovic; S. I. Panagopoulou; I. G. Pallikaris (Case Reports in Ophthalmological Medicine)
Purpose. To present a case of cataract surgery performed in a patient with a refractive corneal inlay in place. Methods. A 48-year-old female patient presented to our institute with bilateral cataract. The patient had undergone refractive corneal inlay implantation three years ago in her right, nondominant eye for presbyopia correction. Biometry and intraocular lens (IOL) power calculation were performed without removing the inlay. Phacoemulsification and IOL insertion were carried out in both eyes in a usual manner. Results. On day one postoperatively, the patient achieved binocular uncorrected distance visual acuity 20/20 and uncorrected near visual acuity J1. The vision remained stable during the one-year follow-up period. Conclusion. Cataract surgery was performed in a standard manner in a patient with Presbia Microlens corneal inlay in place. Visual outcomes for both near and distance vision were satisfactory.